Analisis Pesan Dakwah Dalam Konten Login Melalui Channel Youtube Deddy Corbuzier - Hani, Rima; Mutrofin, Mutrofin (IAINU Kebumen, 2023)
Youtube is usedas a media for da’wah because it is more easily accessible to the public, the use of youtube as a media for da’wah has been widely utilized by famous da’i and has used youtube as a medium for da’wah both directly and by creating content or series. To welcome the holy month of ramadhan, Deddy Corbuzier created a content program “Login” on his youtube channel, Login itself attracted the attention of social media users because it was presented in the form of a dialog conversation between Habib Ja’far and Onadio Leonardo is a non muslim who became the host. The purpose of this study is to analyze how the da’wah message contained in the Login content on Deddy Corbuzier youtube channel. This research uses qualitative research with content analysis methods. The data generated comes from videos on the youtube channel. The results showed that the da’wah messages conveyed by Habib Ja’far in the Login content contained 3 da’wah messages namely aqidah,morals and shari’ah